2015
DOI: 10.4103/0971-9261.145438
|View full text |Cite
|
Sign up to set email alerts
|

Anorectal malformations

Abstract: Anorectal malformations (ARMs) are among the more frequent congenital anomalies encountered in paediatric surgery, with an estimated incidence ranging between 1 in 2000 and 1 in 5000 live births. Antenatal diagnosis of an isolated ARM is rare. Most cases are diagnosed in the early neonatal period. There is a wide spectrum of presentation ranging from low anomalies with perineal fistula having simple management to high anomalies with complex management. Advances in the imaging techniques with improvement in kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
58
0
12

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 25 publications
3
58
0
12
Order By: Relevance
“…Malformations of the anus, anal canal and rectum are relatively common congenital defects, often coexisting in a significant percentage of cases with other congenital anomalies, but as different authors reporting their incidence has major differences in terms of worldwide geographic distribution [1][2][3]7]. Researchers such as de Blaauw and Wijers found that the causes of ARMs are unknown, but some studies demonstrated a genetic predisposition to these conditions [9,10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Malformations of the anus, anal canal and rectum are relatively common congenital defects, often coexisting in a significant percentage of cases with other congenital anomalies, but as different authors reporting their incidence has major differences in terms of worldwide geographic distribution [1][2][3]7]. Researchers such as de Blaauw and Wijers found that the causes of ARMs are unknown, but some studies demonstrated a genetic predisposition to these conditions [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…ARMs include a wide spectrum of inborn defects ranging from perineal fistulas that require a relatively simple modality of treatment to major defects that require complex management. The multiple taxonomy of these lesions (Wingspread, Peña, Kirkenbeck) proposed in the literature is rather confusing, most practitioners currently favoring a classification based on the anatomical criteria depending on the position of the rectal pouch relative to the puborectal sling, associated abnormalities ("syndromic" forms) and the presence or absence of fistulas [2,10,11]. Advances in imaging techniques along with improvements in embryology, morphology and pathogenesis of these lesions have refined both diagnosis and management, moving from classical procedures to PSARP (VUP) and even minimally invasive methods, as discussed by different authors [12][13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In any other case a colostomy is performed as ORIGINAL ARTICLE a diversion and the new born is evaluated using conventional imaging methods (distal colostogram, transperineal ultrasonography) for demonstration of the altered anorectal anatomy. Without this information, an operation in the newborn period is essentially a blind perineal exploration and in turn damage unexpected structures during the search for rectum [2,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…For patients with ARMs, post-operative continence depends on the grade of development of sphincter muscle complex (SMC). Pelvic MRI though not done routinely is the most effective imaging technique for determining the grade of development of SMC [7,8,[15][16][17]. This information will help the medical team make decisions about the definitive surgical approach and provide orientation about the possible post-operative prognosis [2].…”
Section: Introductionmentioning
confidence: 99%